Modeling of Hydrogen Adsorption Phenomenon in Amorphous Silica Using Molecular Dynamics Method - Muhammad Hanif Abdurrahman; J. F. Fatriansyah; D. Dhaneswara; F. R. Kuskendrianto; M. B. Yusuf (Indonesian Journal of Energy, 2020)
Hydrogen is one of the future source energy because it has environmentally friendly. However, there are still some problems in the storage method of hydrogen. In several studies, it was found that Silicon based material is a promising candidate as a hydrogen storage medium. In this study, the effect of various temperature and pressure to the adsorption of hydrogen on amorphous silica with molecular dynamics simulation using Lennard-Jones potential. In this simulation, the temperature that i used are 233, 253, 273 and 293 K with pressure at each temperature are 1, 2, 5, 10, and 15 atm. The simulations had successfully visualized and indicate that amorphous silica has a good hydrogen storage capability where temperature and pressure affect the amount of hydrogen adsorbed. At low temperature (233 K), the hydrogen concentrations are relatively high than at higher temperature. The best result of hydrogen capacity is 0.048116% that occurred at high pressure (15 atm) with low temperature (233 K) condition.*The paper has been selected from a collaboration with IPST and 7th ICFCHT 2019 for a conference entitled "Innovation in Polymer Science and Technology (IPST) 2019 in Conjunction with 7th International Conference on Fuel Cell and Hydrogen Technology (ICFCHT 2019) on October 16th - 19th at The Stones Hotel Legian, Bali, Indonesia"